Pupils’ performance in managing the holistic craft process - Antti Hilmola; Eila Lindfors (Oslo and Akershus University College of Applied Sciences, Learning Centre and Library, 2022)
The Finnish National Board of Education assessed learning outcomes in the final 9th grade of basic education in 2010. This assessment included a design task that involved testing the management of the holistic craft process (HCP), a test of theoretical knowledge and an attitude test. This article revisits the national assessment from a new perspective: to what extent do pupils have the competence to manage HCP, theoretical knowledge and what stand do they take towards the crafts subject in their attitudes? The more specific research questions strive to address: to what extent does theoretical knowledge and attitudes determine the managing of HCP? Is the performance in managing this process dependent on gender and earlier craft studies? This research focuses on a central concept: the competence to manage HCP. The assessment data was marked off into tasks that indicated the managing of HCP (n = 661 out of the sample N = 4,792). K-means cluster analysis, linear regression analysis, crosstabs with the Chi-squared test, and Spearman’s rank order correlation coefficient were used as a methodological solution. The central observation is that three different groups of pupils managed HCP, the theoretical knowledge and the attitudes. These groups are: the positive achievers (43 %), the positive underachievers (29 %) and the negative underachievers (28 %). In addition the performance in managing HCP cannot be determined by the theoretical knowledge and the attitudes in crafts at all, but is rather related to gender and earlier craft studies.